2016
DOI: 10.2196/mhealth.6445
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Facing Mobile Apps to Treat High-Need, High-Cost Populations: A Scoping Review

Abstract: BackgroundSelf-management is essential to caring for high-need, high-cost (HNHC) populations. Advances in mobile phone technology coupled with increased availability and adoption of health-focused mobile apps have made self-management more achievable, but the extent and quality of the literature supporting their use is not well defined.ObjectiveThe purpose of this review was to assess the breadth, quality, bias, and types of outcomes measured in the literature supporting the use of apps targeting HNHC populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 47 publications
1
46
0
1
Order By: Relevance
“…Previous studies identified the main factors of successful outcomes in mHealth interventions for older populations as independence, understanding, and confidence to access complex interventions [13,20]. Tracking features during periodic training and regular follow-ups are essential to provide positive feedback of progression based on objective data obtained during the mHealth intervention [11,35].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies identified the main factors of successful outcomes in mHealth interventions for older populations as independence, understanding, and confidence to access complex interventions [13,20]. Tracking features during periodic training and regular follow-ups are essential to provide positive feedback of progression based on objective data obtained during the mHealth intervention [11,35].…”
Section: Discussionmentioning
confidence: 99%
“…The iPad mini has some advantages regarding (1) proper size and weight to carry; (2) high pixel density in high quality images, which is key for older users to reduce burden due to limited visual difficulty; and (3) opportunities to use diverse types of apps developed internationally [23], as previous literature emphasizes [10,11,20].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations